Isomers of Biologically Active 2-Aminopyrimidinium Picrate through Intrinsic Reaction Coordinate Analysis and Spectroscopic Measurements. (26th November 2022) - Karthick, T.; Singh, Keshav Kumar; Singh, Swapnil; Tandon, Poonam; Narayana, B.
Abstract: In the present study, the isomeric forms of a biologically active 2-aminopyrimidinium picrate (2APP) cocrystal were investigated using spectroscopic measurements (FT-IR and FT-Raman) and density functional theory calculations. The vibrational assignments of IR and Raman peaks were predicted and the experimental FT-IR and FT-Raman spectra of the condensed phase of 2APP were compared with the simulated one. The intrinsic reaction coordinate (IRC) analysis was performed on all the possible reaction pathways to identify the isomeric forms of 2APP and transition state geometry. From the IRC analysis, a relatively stable form (named as isomer 2) has been identified in addition to the existing isomeric form (isomer 1) in the crystalline packing of 2APP. The presence of non-covalent interactions within the isomeric forms of 2APP was investigated with the help of quantum topological atoms in molecules analysis. Reactivity descriptors and charge delocalization from lone pair to acceptor entities of both the isomers were predicted to validate the interactions present in the molecule and also to understand the charge distribution within the molecule.